Easier together: Shared responsibility and corruption - Yuliet Verbel (The University of Nottingham, Centre for Decision Research and Experimental Economics (CeDEx), 2024)
When faced with the choice of behaving corruptly, are people more willing to accept a bribe or to embezzle money? Situations of bribery and embezzlement usually differ in their decision-making dynamics, with bribery requiring coordination between decision-makers (i.e., briber and bribee) while embezzlement does not require such coordination for a decision of corruption. This study makes use of outcome-equivalent games to examine participants' willingness to engage in these two types of corruption. The results show people are more likely to undertake bribery than embezzlement, and this is attributed to the joint decision-making dynamic of bribery, which shapes the responsibility for the outcome of corruption to be shared between the decision-makers instead of concentrated as it is in a situation of embezzlement. In an additional experiment eliciting social norms related to bribery and embezzlement, I find a clear norm of no-corruption, which highlights a discrepancy between the perceived appropriateness of these situations and the actual behavior exhibited in them. I further find that the social appropriateness ratings for each type of corruption are not significantly different. My findings suggest that anticorruption efforts should account for factors that facilitate rule-breaking behavior, such as coordinated decisions that lead to shared responsibility for the outcome.
Keywords: C90; D73; K42; 330; Bribery; Experiment; Embezzlement; Corruption